Paulina Palmer. Queering Contemporary Gothic Narrative 1970-2012. London: Palgrave Macmillan, 2016. - Tanya Gonzalez (Studies in 20th & 21st Century Literature, 2018)
Review of Paulina Palmer's Queering Contemporary Gothic Narrative 1970-2012. London: Palgrave Macmillan, 2016. viii + 204 pp.
Keywords: queer; gothic; narrative; Palmer